Helicon wave plasma generated by a resonant birdcage antenna: magnetic field measurements and analysis in the RAID linear device. (15th July 2021) - Guittienne, Ph; Jacquier, R; Pouradier Duteil, B; Howling, A A; Agnello, R; Furno, I
Abstract: This paper describes a helicon-wave-sustained plasma generated by a novel birdcage antenna with cosine azimuthal current distribution. The resonant birdcage source maintains a stable intense plasma column from low (300 W) to high (10 kW) steady-state RF power in hydrogen or argon, enabling plasma diagnostic measurements over the whole volume. The plasma density, 10 18 to 10 19  m −3, and uniform static magnetic field, 200–800 G, are typical of high density, low B -field helicon sources where the RF excitation frequency, 13.56 MHz here, is far above the ion cyclotron frequency and much lower than the electron cyclotron and plasma frequencies. Magnetic field measurements of the unbounded plasma column show a helicon wave propagating from the birdcage source to the target 1.5 m away. The axial wavelength, measured for a range of plasma density and magnetic field, is described by the whistler dispersion relation; it is not determined by the antenna length but varies smoothly as a function of electron density irrespective of the gas type, and shows no discontinuous transitions. This wavelength was compared with semi-analytical and purely numerical models, showing a good fit with the m = +1 helicon eigenvalue of shortest axial wavelength. The birdcage resonant antenna is a suitable source for continuous helicon-sustained plasma experiments, from fundamental wave studies up to high power applications in hydrogen or deuterium.